Resistência vertical, Resistência específica, Seleção assistida, Proteínas relacionadas à patogênese (PRP) - Pinheiro, Thiago Martins (2011)
Blast (Magnaporthe oryzae) is considered the most important disease of rice fields. Due to the high variability of the pathogen's population, rice cultivars quickly have its race-specific resistance to blast broken. The identification for incorporating different resistance genes in improved and adapted cultivars, utilizing molecular tools, is one breeding strategy to find stable resistance in short period. The goal of this research was to identify the number of resistance genes and SRR molecular markers to the pathotypes IB-1 and IB-9 of M. oryzae, and characterize some enzymes related to the expression of resistance. The experiments were conducted under controlled conditions of green house and laboratories. After crossing cultivar Cica-8 and cultivar Metica-1, the populations F1, F2, BC1:1 and BC2:2 were sown in plastic trays containing five kg of soil fertilized. Each tray contained eight lines with ten plants per row. Each pathotype of M. oryzae inoculated thirty plants of resistant parents, thirty plants of susceptible parents, two hundred plants of F2 population, one hundred plants of BC1:1 population and one hundred plants of BC1:2 population. The isolates 1049 (IB-1) and 435 (IB-9) were cultivated on oat medium to produce the inoculum solution (3.105 conidia.mL-1). The inoculated plants were kept under high humidity condition at 28°C, during seven days. Evaluations were made identifying the number of resistant and susceptible plants. Eleven microsatellite markers were tested by PCR strategies, utilizing DNA of each parent (resistance and susceptible), F1 and F2 populations. PCR reactions were assembled according to the characteristic of each SSR prime. The fragments were separated by denature polyacrylamide (6%) gel to identify polymorphism. Linkage analysis of the RM7102 microssatelite marker was estimated using the MAP MAKER III software. The enzymatic characterization was studied through the extraction of proteins, before and after inoculation, during five consecutive days for the determination of the activity of β-1,3-glucanase (PR1) and peroxidase. Segregation in populations F2 resistant and susceptible presented ratio of 3 plants resistant to 1 plant susceptible. An SSR marker has been identified, RM7102, and linked to the resistance gene of cultivar Cica-8 to the pathotype IB-1. Peroxidase had little activity in all populations. The F2 populations, susceptible to both isolates, presented high β-1,3- glucanase activity.